Pengaruh Syukur terhadap Motivasi Berprestasi Mahasiswa Jurusan Tasawuf Psikoterapi yang Mengalami Fatherless - Elza Sabillah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
Achievement motivation is one of the keys to student success in education. Achievement motivation needs to be supported by a supportive environment. However, not all students are fortunate enough to receive support, especially the presence of a father in their growth process. This study aims to determine the effect of gratitude on the achievement motivation of active students majoring in Sufism and Psychotherapy who have experienced fatherlessness. This study uses a quantitative approach with a sample of 36 students majoring in Sufism and Psychotherapy who have experienced fatherlessness with several established inclusion criteria. The analysis technique used is simple regression analysis. The results of the study show a significant correlation with p = 0.001 (p <0.05) and rxy: 0.565, meaning that gratitude affects student achievement motivation. Thus, it can be concluded that the higher the level of gratitude, the higher the achievement motivation. The R square value was 0.319, indicating that gratitude contributed or influenced 31.9% of achievement motivation. The remaining 68.1% of achievement motivation was influenced by other factors not examined in this study.